ILMU USHUL FIQH (Kajian Ontologis dan Aksiologis) - Muhyar Fanani (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
At first, Islamic law is a law which encompasses all aspects of life. In reality, Islamic law only becomes a marginal law. Most of observers said that its fault is on the methodology aspect that is Islamic legal theory. Therefore, the effort of this theory development cannot be avoided. The figures of Islamic legal theory such as Fazlur Rahman (Pakistan), Mahmoud Muhammad Taha (Sudan), Abdullahi Ahmed an-Na’im (Sudan- USA), Muhammad Sa’id Asymawi (Egypt), and Abd al-Hamid A. Sulaymân (Arab-Malay) remind Moslems to develop this theory. This writing tries to accept their invitation based on philosophy perspective, that is a perspective which has not been used by them.